Autism and the synapse. Issue 2 (April 2015) - Ebrahimi-Fakhari, Darius; Sahin, Mustafa
<x xml:space="preserve">Abstract</x> Purpose of review Recent studies have implicated hundreds of genetic variants in the cause of autism spectrum disorder (ASD). Genes involved in 'monogenic' forms of syndromic ASD converge on common pathways that are involved in synaptic development, plasticity and signaling. In this review, we discuss how these 'developmental synaptopathies' inform our understanding of the molecular disease in ASD and highlight promising approaches that have bridged the gap between the bench and the clinic. Recent findings Accumulating evidence suggests that synaptic deficits in syndromic and nonsyndromic ASD can be mapped to gene mutations in pathways that control synaptic protein synthesis and degradation, postsynaptic scaffold architecture and neurotransmitter receptors. This is recapitulated in models of Fragile X syndrome (FXS), Tuberous Sclerosis Complex (TSC), Angelman syndrome and Phelan-McDermid syndrome (PMS), all of which cause syndromic ASD. Important recent advances include the development of mouse models and patient-derived induced pluripotent stem cell (iPSC) lines that enable a detailed investigation of synaptic deficits and the identification of potential targets for therapy. Examples of the latter include mGluR5 antagonists in FXS, mTOR inhibitors in TSC and insulin-like growth factor 1 (IGF-1) in PMS. Summary Identifying converging pathways in syndromic forms of ASD will uncover novel therapeutic targets for non-syndromic ASD. Insights into developmental synaptopathies will lead to rational development of mechanism-based therapies and clinical trials that may provide a blueprint for other common pathways implicated in the molecular neuropathology of ASD.